Vapor pressure deficit control and mechanical vibration techniques to induce self-pollination in strawberry flowers - Hyein Lee; Meiyan Cui; Byungkwan Lee; Jeesang Myung; Jaewook Shin; Changhoo Chun (Plant Methods)
Abstract Background Pollination strategies to supplement or replace insect pollinators are needed to produce marketable strawberry fruits in indoor vertical farms. To ensure the self-pollination of strawberry flowers, anther dehiscence, and pollen attachment were investigated under different vapor pressure deficit (VPD) conditions and external mechanical wave vibrations. Results The proportion of dehisced anthers was examined under VPDs of 2.06, 1.58, and 0.33 kPa, and the projected area of pollen clumps was assessed under VPDs of 2.06 and 0.33 kPa. After exposing flowers to a VPD of 2.06 kPa, vibrations with various frequency (Hz) and root mean square acceleration (m s−2) combinations were used to evaluate pollination effectiveness. The anthers underwent complete dehiscence at VPDs of 2.06, 1.58, and 0.33 kPa. The pollen clump ejection index was highest at a VPD of 2.06 kPa. Pollen clump detachment was effective at 800 Hz with 40 m s−2, while pollen attachment to the stigma was most effective at 100 Hz with 30 and 40 m s−2. Conclusions These findings demonstrate that high VPD promotes anther dehiscence timing and facilitates pollen clump formation, while specific vibration frequencies with high acceleration optimize pollen detachment and stigma attachment, offering an effective strategy for controlled strawberry pollination in vertical farming.